Mandatory Physician Reporting of At-Risk Drivers: The Older Driver Example. (9th January 2017) - Agimi, Yll; Albert, Steven M; Youk, Ada O; Documet, Patricia I; Steiner, Claudia A
Abstract: Purpose of the Study: In a number of states, physicians are mandated by state law to report at-risk drivers to licensing authorities. Often these patients are older adult drivers who may exhibit unsafe driving behaviors, have functional/cognitive impairments, or are diagnosed with conditions such as Alzheimer's disease and/or seizure disorders. The hypothesis that mandatory physician reporting laws reduce the rate of crash-related hospitalizations among older adult drivers was tested. Design and Methods: Using retrospective data (2004–2009), this study identified 176, 066 older driver crash-related hospitalizations, from the State Inpatient Databases. Three age-specific negative binomial generalized estimating equation models were used to estimate the effect of physician reporting laws on state's incidence rate of crash-related hospitalizations among older drivers. Results: No evidence was found for an independent association between mandatory physician reporting laws and a lower crash hospitalization rate among any of the age groups examined. The main predictor of interest, mandatory physician reporting, failed to explain any significant variation in crash hospitalization rates, when adjusting for other state-specific laws and characteristics. Vision testing at in-person license renewal was a significant predictor of lower crash hospitalization rate, ranging from incidence rate ratio of 0.77 (95% confidence interval 0.62–0.94) among 60- to 64-year olds to 0.83 (95% confidence interval 0.67–0.97) among 80- to 84-year olds. Implications: Physician reporting laws and age-based licensing requirements are often at odds with older driver's need to maintain independence. This study examines this balance and finds no evidence of the benefits of mandatory physician reporting requirements on driver crash hospitalizations, suggesting that physician mandates do not yet yield significant older driver safety benefits, possibly to the detriment of older driver's well-being and independence.